2017
DOI: 10.1507/endocrj.ej17-0128
|View full text |Cite
|
Sign up to set email alerts
|

C1qTNF-related protein 1 improve insulin resistance by reducing phosphorylation of serine 1101 in insulin receptor substrate 1

Abstract: C1qTNF-related protein 1 (CTRP1) is independently associated with type 2 diabetes. However, the relationship between CTRP1 and insulin resistance is still not established. This study aimed to explore the role of CTRP1 under the situation of insulin resistance in adipose tissue. Plasma CTRP1 level was investigated in type 2 diabetic subjects (n = 35) and non-diabetic subjects (n = 35). The relationship between CTRP1 and phosphorylation of multi insulin receptor substrate 1 (IRS-1) serine (Ser) sites was further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Previous studies suggested that members of CTRP superfamily, including adiponectin, CTRP1, CTRP3, CTRP5, CTRP6, and CTRP15, are involved in the regulation of several metabolic and inflammatory pathways. For instance, CTRP1 forms an oligo‐heterotrimer with CTRP6, and is known to enhance glucose uptake and insulin sensitivity . Elevated levels of CTRP1 have been associated with BMI, T2DM, nonalcoholic fatty liver disease (NAFLD), congestive heart failure (CHF), and chronic kidney disease progression .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that members of CTRP superfamily, including adiponectin, CTRP1, CTRP3, CTRP5, CTRP6, and CTRP15, are involved in the regulation of several metabolic and inflammatory pathways. For instance, CTRP1 forms an oligo‐heterotrimer with CTRP6, and is known to enhance glucose uptake and insulin sensitivity . Elevated levels of CTRP1 have been associated with BMI, T2DM, nonalcoholic fatty liver disease (NAFLD), congestive heart failure (CHF), and chronic kidney disease progression .…”
Section: Discussionmentioning
confidence: 99%
“…The C1QTNF family has a highly conserved c-terminal complementary C1q domain consisting of 16 CTRP members, including C1QTNF 1-9,9b, 10-15 [13]. All C1QTNF members are secreted proteins that are widely expressed in a variety of tissues and cell types and are involved in a variety of biological processes, including host defense, in ammation, apoptosis, autoimmunity, cell differentiation, organogenesis, hibernation, and insulin-resistant obesity [14][15][16][17][18][19]. C1QTNF6, as a member of C1QTNF family, was demonstrated to be associated with carcinogenesis in digestive cancers, however, the biological functions in bladder cancer still required investigating.…”
Section: Discussionmentioning
confidence: 99%
“…25 It is reported that GLP-1 receptor agonist, the novel antidiabetic drug (Ex-4), can improve lipid deposition in hepatocytes. 26,27 Studies indicated that activation of the central nerve system GLP-1 receptor improves T2DM via glucose metabolism dependent inhibition of central nerve system AMPK. 28 AMPK activation accelerate fatty acid oxidation and glucose uptake, suppresses triglycerides production in skeletal muscle,which is necessary for the body to maintain the balance of blood glucose.…”
Section: Discussionmentioning
confidence: 99%